HUBUNGAN ANTARA PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP TINGKAT PENGANGGURAN TERBUKA SERTA IMPILIKASINYA TERHADAP KEMISKINAN DI INDONESIA - melindawati; Michael; Muhammad Awaluddin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the relationship between economic growth andinflation on the open unemployment rate and its implications for poverty inIndonesia based on the Phillips Curve approach and Okun's Law, whether thePhillips Curve Theory and Okun's Law apply in Indonesia. The Phillips curvestates that there is a relationship or trade off between the inflation rate and theunemployment rate. Okun's law states that there is a linear negativerelationship between unemployment and economic growth: a 1% increase in the unemployment rate will cause a decrease in economic growth by 2% or more,whereas a 1% increase in output will cause a decrease in the unemploymentrate of 1% or less. Based on the results of Granger causality for the case of theIndonesian economy during the period 2001-2020, it shows that there is notrade off relationship between inflation and open unemployment as depicted inthe Philips Curve. Furthermore, based on the difference version method ofOkun's law to obtain Okun's coefficient and Ordinary Least Square (OLS)analysis, it is known that there is no negative relationship betweenunemployment and the rate of economic growth in Indonesia during the period2001-2020 and vice versa. And based on time series regression analysis withthe lag distribution method, using the Koyck model, it is obtained that economicgrowth, inflation and open unemployment affect poverty in Indonesia